ABS / POK composite material as well as preparation method and application thereof

By introducing POK resin into ABS resin and combining maleic anhydride-styrene random copolymer and chlorinated polyethylene, the compatibility of ABS and POK is improved, and the swelling problem and insufficient hardness of ABS materials in chemical solvents are solved, and the soft feel and chemical resistance of ABS/POK composites are achieved.

CN119798913AActive Publication Date: 2025-04-11KINGFA SCI & TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411989390.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

ABS materials are prone to swelling and breaking in non-polar oils or chemical solvents, and have high hardness, which cannot meet the requirements of some products that require soft feel. Direct blending ABS and POK materials have poor compatibility, poor performance and appearance.

Method used

POK resin is introduced into ABS resin, and the compatibility of ABS and POK is improved by adding maleic anhydride-styrene random copolymer and chlorinated polyethylene with specific Mooney viscosity, reducing the crystallinity of POK, enhancing the softness and chemical resistance of the material.

Benefits of technology

It achieves good compatibility and chemical resistance of ABS/POK composite materials, while giving the material a soft and benign feel, suitable for products that require a soft feel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223300410000061
    Figure BDA0005223300410000061
  • Figure BDA0005223300410000071
    Figure BDA0005223300410000071
  • Figure BDA0005223300410000081
    Figure BDA0005223300410000081
Patent Text Reader

Abstract

The invention discloses an ABS / POK composite material as well as a preparation method and application thereof, and relates to the technical field of modified plastics. The invention provides an ABS / POK composite material. The ABS / POK composite material comprises the following components in parts by weight: 40-65 parts of ABS resin, 15-30 parts of POK resin, 15-30 parts of chlorinated polyethylene and 2-5 parts of a maleic anhydride-styrene random copolymer, the Mooney viscosity of the chlorinated polyethylene is 65-80 under the test conditions of ML (1 + 4) and 125 DEG C according to the standard of GB / T 1232.1-2000. The invention provides an ABS / POK composite material with chemical resistance and good hand feeling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of modified plastics, in particular to an ABS / POK composite material and a preparation method and application thereof. Background Art

[0002] ABS resin is a terpolymer composed of styrene, butadiene and acrylonitrile. It has excellent processing performance, low temperature resistance, electrical insulation performance, high gloss and excellent electroplating performance. It also has excellent characteristics such as good creep resistance, high dimensional stability and small molding shrinkage. It is widely used in plastic products in the fields of home appliances, automobiles, electronic appliances, etc. However, ABS material has poor oil resistance and organic solvent resistance. It is easy to swell and break in non-polar oils or chemical solvents. The unsaturated polybutadiene double bonds in the structure are easy to age and discolor, affecting the appearance of the product. This performance defect greatly limits the application and promotion of ABS materials in some product fields. In addition, ABS material has a relatively high hardness. For some handle parts, a softer feel is required, but ABS material cannot meet the requirements. It is usually necessary to spray a feel paint or two-color injection molding for TPE encapsulation to achieve a better feel. POK resin is an aliphatic polyketone resin obtained by copolymerization of carbon monoxide and olefins (generally ethylene and propylene) with good chemical resistance. These two characteristics can just make up for the shortcomings of ABS material. However, when ABS and POK are directly blended, the resulting material has poor compatibility, poor product performance and appearance, and is difficult to be used in practice.

[0003] Therefore, an ABS / POK composite material with good chemical resistance and good hand feel has broad application prospects. Summary of the invention

[0004] Based on this, the purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide an ABS / POK composite material with good chemical resistance and good hand feel, and a preparation method and application thereof.

[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: an ABS / POK composite material, comprising the following components in parts by weight: 40-65 parts of ABS resin, 15-30 parts of POK resin, 15-30 parts of chlorinated polyethylene (CPE), and 2-5 parts of maleic anhydride-styrene random copolymer; the chlorinated polyethylene has a Mooney viscosity of 65-80 under ML (1+4) and 125°C test conditions according to GB / T 1232.1-2000 standard.

[0006] The present invention introduces aliphatic polyketone (POK) resin into ABS resin, and through the addition of maleic anhydride-styrene random copolymer, the anhydride reacts with the carbonyl group of POK to reduce the crystallinity of POK and weaken the interface between amorphous ABS and semi-crystalline POK. At the same time, the addition of chlorinated polyethylene with a specific Mooney viscosity makes the PE segment in the chlorinated polyethylene have good compatibility with the olefin segment in POK, further improving the compatibility of ABS and POK. At the same time, the softness and elasticity of the chlorinated polyethylene make the ABS alloy material present a soft and good feel. If the Mooney viscosity of the chlorinated polyethylene is too low, the shearing during the modification process is small, it is not easy to disperse evenly, and the skin feel is poor; if the Mooney viscosity of the chlorinated polyethylene is too high, the material fluidity is poor, it is difficult to injection mold, and the skin feel is rough.

[0007] Preferably, the weight percentage of the ABS resin in the ABS / POK composite material is not less than 40%.

[0008] Preferably, the ABS / POK composite material comprises the following components in parts by weight: 50-60 parts of ABS resin, 20-25 parts of POK resin, 20-25 parts of chlorinated polyethylene, and 3-4 parts of maleic anhydride-styrene random copolymer.

[0009] Optionally, the weight of the ABS resin is in the range of 40, 45, 50, 55, 58, 60, 61, 63, 65 parts or any two of the range values; the weight of the POK resin is in the range of 15, 18, 20, 21, 23, 25, 28, 30 parts or any two of the range values; the weight of the chlorinated polyethylene is in the range of 15, 18, 20, 21, 23, 25, 28, 30 parts or any two of the range values; the weight of the maleic anhydride-styrene random copolymer is in the range of 2, 3, 4, 5 parts or any two of the range values.

[0010] Optionally, the Mooney viscosity of the chlorinated polyethylene under ML (1+4) and 125° C. test conditions according to GB / T 1232.1-2000 standard is within the range of one or any two of 65, 68, 70, 72, 75, and 80.

[0011] Preferably, the rubber content of the ABS resin is ≥18wt%; further preferably, the rubber content of the ABS resin is 25-35wt%. The rubber content of the present invention is determined by high-speed centrifugal separation, and the specific steps are as follows:

[0012] Weigh 1.000g of the dried ABS and weigh the reagent bottle m1;

[0013] (1) Place ABS in a reagent bottle, add about 25 ml of acetone, and ultrasonically vibrate for 3 hours;

[0014] (2) Place in a high-speed centrifuge and centrifuge for 30 min at a speed of >15000 r / min;

[0015] (3) Immediately after centrifugation, remove the acetone with a syringe, taking care not to remove the solids;

[0016] (4) Add 25 ml of acetone again and ultrasonically shake for 3 h;

[0017] (5) centrifuging again and removing the acetone solution after centrifugation;

[0018] (6) Place the reagent bottle in a vacuum oven at 80°C and dry for 10 h;

[0019] (7) Cool to room temperature and weigh m2;

[0020] (8) Rubber content = (m2-m1) / 1*100wt%.

[0021] Preferably, the POK resin has a melt flow rate of ≥60 g / 10 min at 240° C. and 2.16 kg according to ISO 1133-1-2011. Further preferably, the POK resin has a melt flow rate of 60-200 g / 10 min at 240° C. and 2.16 kg according to ISO 1133-1-2011.

[0022] Preferably, the mass percentage of maleic anhydride in the maleic anhydride-styrene random copolymer is 15-27%. Further preferably, the mass percentage of maleic anhydride in the maleic anhydride-styrene random copolymer is 15-23%.

[0023] Optionally, the rubber content of the ABS resin is in a range of one or any two of 18wt%, 20wt%, 23wt%, 25wt%, 27wt%, 33wt%, 33wt%, 35wt%.

[0024] Optionally, the melt flow rate of the POK resin is in the range of one or any two of 60 g / 10 min, 68 g / 10 min, 80 g / 10 min, 100 g / 10 min, 120 g / 10 min, 150 g / 10 min, and 200 g / 10 min.

[0025] Optionally, the mass percentage of maleic anhydride in the maleic anhydride-styrene random copolymer is in the range of one or any two of 15%, 18%, 20%, 23%, 25%, 27%.

[0026] Preferably, the mass percentage of maleic anhydride in the present invention can be determined by infrared spectroscopy: a sample of fixed thickness is tested using a Fourier transform infrared spectrometer to obtain a characteristic absorption peak of the infrared spectrum, and the mass percentage of maleic anhydride can be calculated by comparing the ratio of the carbonyl and methylene absorption intensities.

[0027] Preferably, the ABS / POK composite material further comprises 0.5-2 parts of a stabilizer, 0.5-2 parts of an antioxidant and 0.5-2 parts of a lubricant.

[0028] Optionally, the stabilizer is at least one of a calcium zinc stabilizer, a barium zinc stabilizer, and an organic tin stabilizer.

[0029] Optionally, the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant, such as Antioxidant 168 (tris[2,4-di-tert-butylphenyl]phosphite), Antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), and the like.

[0030] Optionally, the lubricant is at least one of stearates, stearic acid esters, and ethylene bis stearic acid amides, such as pentaerythritol stearate, zinc stearate, and the like.

[0031] In addition, the present invention provides a method for preparing the ABS / POK composite material, comprising the following steps: mixing the components in proportion, melt-extruding, and granulating to obtain the ABS / POK composite material.

[0032] Preferably, in the preparation method of the ABS / POK composite material, the extrusion temperature is 80-230° C., the screw speed is 300-400 rpm, and the aspect ratio of the extruder is 48:1.

[0033] Furthermore, the present invention provides application of the ABS / POK composite material in the field of electronic appliances or household appliances.

[0034] Preferably, the present invention provides the use of the ABS / POK composite material in a game controller, a vacuum cleaner handle, and a refrigerator handle.

[0035] Compared with the prior art, the present invention has the following beneficial effects: the present invention introduces aliphatic polyketone (POK) resin into ABS resin, and through the addition of maleic anhydride-styrene random copolymer, the anhydride reacts with the carbonyl group of POK to reduce the crystallinity of POK and weaken the interface between amorphous ABS and semi-crystalline POK. At the same time, the addition of chlorinated polyethylene with a specific Mooney viscosity and the good compatibility of the PE segment in the chlorinated polyethylene with the olefin segment in POK further improve the compatibility of ABS and POK. At the same time, the softness and elasticity of the chlorinated polyethylene make the ABS / POK composite material present a soft, good feel and chemical resistance. DETAILED DESCRIPTION

[0036] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Its purpose is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the experimental reagents and instruments designed for the implementation and comparative examples of the present invention are all commonly used ordinary reagents and instruments, which can be obtained from commercial channels. In the implementation and comparative examples, the experimental methods used are conventional methods unless otherwise specified; and unless otherwise specified, the raw materials used in parallel experiments are the same batch of raw materials.

[0037] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:

[0038] ABS resin-1: rubber content is 25wt%, brand ABSDG-417, manufacturer Tianjin Dagu Chemical;

[0039] ABS resin-2: rubber content is 30wt%, brand ABS 780A, manufacturer is Kumho, South Korea;

[0040] ABS resin-3: rubber content is 35wt%, brand ABSD-120A, manufacturer is Guoqiao, Taiwan, China;

[0041] ABS resin-4: rubber content is 20wt%, brand ABS PA-757, manufacturer is Chimei, Taiwan, China;

[0042] ABS resin-5: rubber content is 39wt%, brand ABSDG-MG29, manufacturer Tianjin Dagu Chemical;

[0043] POK resin-1: melt flow rate 60 g / 10 min (240°C / 2.16 kg), brand POKETONE M330F, manufacturer Hyosung Chemical Corporation;

[0044] POK resin-2: melt flow rate 68 g / 10 min (240°C / 2.16 kg), brand POKETONE M33-R3A000, manufacturer Hyosung Chemical Corporation;

[0045] POK resin-3: melt flow rate 200 g / 10 min (240°C / 2.16 kg), brand POKETONE M130F, manufacturer Hyosung Chemical Corporation;

[0046] Chlorinated polyethylene-1: Mooney viscosity 55 (ML (1+4) / 125°C), Weipren 6335, manufacturer Weifang Yaxing Chemical Co., Ltd.;

[0047] Chlorinated polyethylene-2: Mooney viscosity 65 (ML (1+4) / 125°C), Weipren 6135, manufacturer Weifang Yaxing Chemical Co., Ltd.;

[0048] Chlorinated polyethylene-3: Mooney viscosity 80 (ML (1+4) / 125°C), Weipren 6235, manufacturer Weifang Yaxing Chemical Co., Ltd.;

[0049] Chlorinated polyethylene-4: Mooney viscosity 100 (ML (1+4) / 125°C), Weipren 140B, manufacturer Weifang Yaxing Chemical Co., Ltd.;

[0050] Maleic anhydride-styrene random copolymer-1: the mass percentage of maleic anhydride is 18%, brand SMA700, manufacturer Jiaxing Huawen;

[0051] Maleic anhydride-styrene random copolymer-2: the mass percentage of maleic anhydride is 23%, the brand is SZ23110, the manufacturer is Polyscope Company of the Netherlands;

[0052] Maleic anhydride-styrene random copolymer-3: The mass percentage of maleic anhydride is 25%, brand SMA-725, manufacturer Jiaxing Huawen;

[0053] Stabilizer: Calcium zinc stabilizer RUP-108, Aidico Fine Chemical Co., Ltd.;

[0054] Lubricant: zinc stearate, commercially available;

[0055] The antioxidant is a composite of a commercially available hindered phenol antioxidant 1010 and a commercially available phosphite antioxidant 168 in a mass ratio of 1:1.

[0056] Examples and Comparative Examples

[0057] The components and weight proportions of the ABS / POK composite material in the embodiments of the present invention and the comparative examples are shown in Table 1-2. The preparation method of the ABS / POK composite material comprises the following steps: mixing the components in proportion, melt extruding, and granulating to obtain the ABS / POK composite material. The melt extrusion conditions are: 80°C in zone 1, 160°C in zone 2, 180°C in zone 3, 230°C in zone 4, 230°C in zone 5, 230°C in zone 6, 220°C in zone 7, 220°C in zone 8, 220°C in zone 9, 220°C in zone 10, 220°C in zone 11, 230°C in die head, 350rpm screw speed, and 48:1 aspect ratio of the twin-screw extruder.

[0058] Performance Testing

[0059] (1) Rockwell hardness: Tested according to GB / T 230.1-2004 Rockwell hardness test method, the test sample is a 6mm thick and diameter disc. The Rockwell hardness is controlled between 70-80.

[0060] (2) Dynamic friction coefficient: Tested in accordance with ASTM D1894-2014 "Standard Test Method for Static and Dynamic Coefficient of Friction of Plastic Film and Sheeting". The dynamic friction coefficient should be controlled at 0.15-0.25. If it is too high, it will produce a noticeable sense of stiffness. If it is too low, the smoothness will be too good and will cover up the softness, thus showing only the smoothness.

[0061] (3) Skin feel evaluation: The skin feel of the sample is mainly affected by the dynamic friction coefficient and Rockwell hardness. To achieve a suitable skin feel, the dynamic friction coefficient should be controlled at 0.15-0.25, and the Rockwell hardness should be between 70-80. In addition, a touch panel was used to evaluate the skin feel for evidence. Specifically as follows: 5 trained and screened judges were used as judges of the touch panel to evaluate the feeling after touching the sample, mainly by sliding the finger on the surface of the sample with moderate force to evaluate. Level 1 represents a smooth and soft touch similar to the skin, level 5 represents a sticky and hard touch, and levels 2-4 represent different levels of change from smooth and soft to sticky and hard. Levels 1-5 correspond to the best, better, moderate, poor, and very poor skin feel, respectively. The average value is taken based on the evaluation results of the 5 people, and the average value is rounded off as the evaluation result. The skin feel of the present invention must at least reach better or better, that is, level 2 or below.

[0062] (4) Chemical resistance test: According to BS EN ISO 22088-3-2006, a standard tensile specimen was loaded into a fixture with a strain of 1.5%, and the surface cracking of the tensile specimen was observed after coating with glacial acetic acid. The chemical resistance evaluation grades are as follows: excellent, no change after 48 hours, recorded as ●; good, tiny silver streaks after 48 hours, recorded as ○; qualified, cracks within 48 hours, recorded as △; poor, cracking and damage within 48 hours, recorded as X.

[0063] The test results are shown in Tables 1 and 2.

[0064] Table 1

[0065]

[0066]

[0067]

[0068] Table 2

[0069] Components (parts by weight) Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 ABS resin-1 50 50 50 50 POK resin-1 20 20 20 20 Chlorinated Polyethylene-2 0 0 20 0 Chlorinated Polyethylene-1 20 0 0 0 Chlorinated Polyethylene-4 0 20 0 0 Maleic anhydride-styrene random copolymer-1 3 3 0 3 SEBS 0 0 0 20 Maleic Anhydride Grafted SEBS 0 0 3 0 Calcium zinc stabilizer 1 1 1 1 Lubricants 1 1 1 1 Antioxidants 1 1 1 1 Rockwell hardness 85 64 76 77 Dynamic friction coefficient 0.29 0.28 0.25 0.31 Skin feel evaluation 5 5 4 5 Chemical resistance ○ ● △ X

[0070] The ABS / POK composite material prepared in the embodiment of the present invention has a Rockwell hardness of 70-80, a dynamic friction coefficient of 0.15-0.25, a skin feel evaluation grade of 2 or below, and a skin feel of good or above.

[0071] From the comparison of Examples 1-5, it can be seen that the rubber content of the ABS resin has a greater influence on the Rockwell hardness and skin feel of the ABS / POK composite material. When the rubber content of the ABS resin is 25-35wt%, the hardness is more moderate and the skin feel evaluation is better.

[0072] From the comparison of Example 1, Example 8, and Comparative Examples 1-2, it can be seen that the Mooney viscosity of chlorinated polyethylene has a great influence on Rockwell hardness, dynamic friction coefficient and skin feel. When the Mooney viscosity of chlorinated polyethylene is 65-80, the Rockwell hardness of the ABS / POK composite material is appropriate, the dynamic friction coefficient is appropriate, the skin feel evaluation level is 2 or below, and the skin feel is good or above. If the Mooney viscosity of chlorinated polyethylene is too low, the shearing during the modification process is small, it is not easy to disperse evenly, and the skin feel is poor; if the Mooney viscosity of chlorinated polyethylene is too high, the material fluidity is poor, it is difficult to injection mold, and the skin feel is rough.

[0073] From the comparison of Example 1, Examples 11-13, and Comparative Examples 3-4, it can be seen that when the ABS / POK composite material contains 50-60 parts of ABS resin, 20-25 parts of POK resin, 20-25 parts of chlorinated polyethylene, and 3-4 parts of maleic anhydride-styrene random copolymer, the hardness is appropriate, the dynamic friction coefficient is appropriate, the skin feel evaluation level is 2 or below, the skin feel is good or above, and the chemical resistance is better.

[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. An ABS / POK composite material, characterized in that: The invention comprises the following components in parts by weight: 40-65 parts of ABS resin, 15-30 parts of POK resin, 15-30 parts of chlorinated polyethylene, and 2-5 parts of maleic anhydride-styrene random copolymer; the Mooney viscosity of the chlorinated polyethylene is 65-80 under the test conditions of ML (1+4) and 125° C. according to GB / T 1232.1-2000 standard.

2. The ABS / POK composite material according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 50-60 parts of ABS resin, 20-25 parts of POK resin, 20-25 parts of chlorinated polyethylene and 3-4 parts of maleic anhydride-styrene random copolymer.

3. The ABS / POK composite material according to claim 1, characterized in that: The rubber content of the ABS resin is ≥18wt%; preferably, the rubber content of the ABS resin is 25-35wt%.

4. The ABS / POK composite material according to claim 1, characterized in that: The POK resin has a melt flow rate of ≥60 g / 10 min at 240° C. and 2.16 kg according to ISO 1133-1-2011.

5. The ABS / POK composite material according to claim 1, characterized in that: The mass percentage of maleic anhydride in the maleic anhydride-styrene random copolymer is 15-27%.

6. The ABS / POK composite material according to claim 1, characterized in that: The ABS / POK composite material also includes 0.5-2 parts of a stabilizer, 0.5-2 parts of an antioxidant and 0.5-2 parts of a lubricant.

7. A method for preparing the ABS / POK composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The components are mixed in proportion, melt-extruded, and granulated to obtain the ABS / POK composite material.

8. Use of the ABS / POK composite material according to any one of claims 1 to 6 in the field of electronic appliances or household appliances.

9. Use of the ABS / POK composite material according to any one of claims 1 to 6 in a game controller, a vacuum cleaner handle, or a refrigerator handle.

Citation Information

Patent Citations

  • Flame-retarding ABS / POK alloy and its preparation method

    CN107903567A

  • High-performance flame-retardant ABS composite material and preparation method thereof

    CN110343382A

  • ABS / POK composite material and preparation method thereof

    CN110372988A

  • PVC / POK composite material for building plastic template and forming method of PVC / POK composite material

    CN115960422A

  • Thermoplastic resin composition, and molded article thereof

    JP2013166842A